Dietary intervention protocol: my body is fit and fabulous at home - mybff@home mobile application (a virtually coach weight loss among housewives) - Idris, Sakinah; Abdul Khaiyom, Jamilah Hanum; Abdul Karim, Samihah; Ismail, Siti Norfatihah; Ismail, Marina; Ismail, Zaliha; Omar, Siti Aminah; Aris, Tahir (Department of Psychiatry Hospital UiTM 42300 Bandar Puncak Alam Puncak Alam, Selangor, 2022)
This module book aims to share knowledge about weight management as well as cognitive and behavior skills that can be used daily. This module book is suitable to be used by individuals, psychologists, or doctors who are interested in helping patients to combat obesity. This book contains a complete protocol on the procedures and techniques used in the study of My Body is Fit and Fabulous at home (MyBFF@home) mobile application: A virtually coach weight loss among housewives. Information is given on diet, physical activities and exercise as well as cognitive behavior therapy that can help an individual to lose weight and subsequently lead to a healthy lifestyle. This book is written in simple language so that all groups can understand and practice the techniques given to gain the ideal weight.